Faire du bruit sans faire de vagues - Jean-Baptiste Comby (Communication)
French civil servants tasked with convincing the population to change their behaviour in order to reduce the emission of greenhouse gases do not take into account the unequal contribution of social groups to the climate problem. Interviews with the campaign managers of the Agency for Environment and Energy Management and a content analysis of the agency’s information campaigns reveal that their public messages obscure the social and political causes linked to the problems of climate change.